Franco Modigliani and oligopoly - Sylos Labini, Paolo (PSL Quarterly Review, 2012)
Modigliani became interested in Keynes's General Theory even before knowing anything about economics. After becoming a professional economist, through his research both theoretical and applied, his teaching, his policy recommendations to fight mass unemployment, Modigliani became worldwide known as one of the great Keynesian economists. Yet, there are many building blocks of Keynes's General Theory that in Modigliani's work cannot be found. In this lecture, it is shown that his pursuit of the task of "digesting"–as he put it–Keynesian innovative ideas into the theoretical framework of Walrasian economics entails the loss of Keynes's genuine revolutionary ideas. The author argues–with some personal recollections–that Keynes's conviction of the necessity of a radically novel "monetary theory of production" remains as relevant today as it was when originally proposed. More than attempting to "digest" the Keynesian revolution, we should attempt to make it fully accomplished. JEL Codes: B21, B22, B31, D43, E00